Information Technology Based Guidance & Counseling Services - Muhammad Risqi Aufaqi Akrom (Universitas Islam Cordoba Banyuwangi, 2025)
Guidance & counseling services are currently closely related to the use of technology and information in practice. The importance of this research is to examine the process of guidance & counseling services using information technology. The purpose of this research is to find out and examine related services in guidance & counseling which are also focused on information technology-based. The results of this research are that guidance & counseling is a process of providing assistance carried out by guidance & counseling teachers to students with the aim of being able to choose and determine decisions, decisions that will be chosen in the process of solving their problems in everyday life and also to achieve their developmental tasks and become sufficient provisions for future life. There are several services and areas of guidance in guidance & counseling. So in practice in implementing the service process, it can also use information technology, this is because the development and sophistication of existing technology can assist the service process and can help guidance & counseling teachers in implementing services effectively and efficiently.